Photosystem II is a chimera of reaction centers - Cardona,Londono T (Journal of Molecular Evolution, 2017)
A complete scenario for the evolution of photosynthesis must account for the origin and diversification of photochemical reaction centers. Two lively debated questions are how the distinct types of reaction centers evolved and how cyanobacteria acquired two distinct reaction centers—Photosystem I and Photosystem II—in the path towards the origin of light-driven water oxidation, or in other words, towards the evolution of oxygenic photosynthesis (Hohmann-Marriott and Blankenship 2011; Fischer et al. 2016). Here I show how the chimeric structure of Photosystem II provides unambiguous answer to these questions.